OCT-Angiography in Detecting Preclinical Diabetic Retinopathy - A. N. Stulova; N. S. Semenova; A. V. Zheleznyakova; V. S. Akopyan; D. S. Lipatov (Oftalʹmologiâ, 2022)
The introduction of OCT-angiography was a milestone in studying the early stages of diabetic retinopathy (DR). The latest findings show significant changes in foveal avascular zone (FAZ) parameters (FAZ area, FAZ perimeter, acirculatory index, axis ratio, FAZ angle) in diabetes mellitus (DM) patients with no ophthalmoscopic signs of DR. Many research groups evaluate vessel density (VD) in superficial and deep plexuses in these patients using different methods of image postprocessing, different qualitative and quantitative parameters. Nonperfusion areas (NA) are very important findings at the preclinical stage of DR, which can be detected in superficial and deep layers. With OCT-A it is possible not only to reveal them but also to calculate their area. Vascular tortuosity (VT) was described earlier using fundus photography. Nowadays VT can be assessed at the microcirculation level in OCT-A scans. Microaneurysms are the earliest clinical sign of DR. They can be missed in fundus photos, but easily detected with OCT-A. The aim of the current review is to analyze the latest OCT-A findings at the preclinical stage of DR and to discuss the future diagnostic value of OCT-A in DR.